Conochironomus (Diptera: Chironomidae) in Asia: new and redescribed species and vouchering issues - Cranston, Peter S. (Zootaxa, 2016)
The presence of the Afro-Australian genus Conochironomus Freeman, 1961 (Diptera: Chironomidae) in Asia has been recognised only informally. An unpublished thesis included Conochironomus from Singapore, and the genus has been keyed from Malaysia without named species. Here, the Sumatran Conochironomus tobaterdecimus (Kikuchi & Sasa, 1980) comb. n. is recorded from Singapore and Thailand. The species is transferred from Sumatendipes Kikuchi & Sasa, 1980, rendering the latter a junior synonym (syn. n.) of Conochironomus Freeman. Conochironomus nuengthai sp. n. and Conochironomus sawngthai sp. n. are described as new to science, based on adult males from Chiang Mai, Thailand. All species conform to existing generic diagnoses for all life stages, with features from male and female genitalia, pupal cephalic tubercles and posterolateral ‘spurs’ of tergite VIII providing evidence for species distinction. Some larvae are linked to C. tobaterdecimus through molecular barcoding. Variation in other larvae, which clearly belong to Conochironomus and are common throughout Thailand, means that they cannot be segregated to species. Larval habitats include pools in river beds, urban storage reservoirs, drains with moderately high nutrient loadings, and peat swamps. Endochironomus effusus Dutta, 1994 from north-eastern India may be a congener but may differ in adult morphology, thereby precluding formal new combination until discrepancies can be reconciled. Many problems with vouchering taxonomic and molecular material are identified that need to be rectified in the future.